TANGGUNG JAWAB NEGARA TERHADAP PERLINDUNGAN DAN KEAMANAN DIPLOMAT DITINJAU DARI HUKUM INTERNASIONAL (STUDI KASUS PENEMBAKAN DUTA BESAR RUSIA DI TURKI) - Sitti Yunike Allysha; Sutiarnoto Sutiarnoto; Arif Arif (Journal of USU International Law, 2018)
ABSTRACT Sitti Yunike Allysha* Dr. Sutiarnoto, S.H.,M.Hum** Arif, S.H.,M.Hum*** International Relations became one of the important aspects of the state, one of the ways is through the practice of diplomatic relations. In general, this practice is done by sending diplomatic representatives of a state to a foreign state, which is then granted immunity rights and guarantees for their safety, as provided by the Vienna Convention 1961. But in fact, the violation of these immunities and guarantees are still happening, one example of this case is the shooting of Russian ambassador for Turkey in Turkey in 2016. The issues raised in this study are how the rights and obligations of the sending state to the diplomatic missions of the foreign state, how the responsibility of a receiving state to the security and safety of diplomats and how is the settlement of the shooting of Russian ambassador to Turkey in Turkey in terms of the Vienna Convention 1961. The methodological approach used in this research study is the normative-legal research method. Firstly, this study was conducted using primary legal sources, such as analyzing the law and its codifications related to this study. Then the secondary legal sources, such as books, scientific journals, magazines, articles, and so on, as well as tertiary legal sources, such as dictionaries. The data collection techniques used in this research study was the library research. The conclusions which can be drawn from this research study are, in accordance to the Vienna Convention 1963, the foreign diplomatic representative has privileges and immunities which shall be respected by the receiving state. The receiving state has the responsibility to ensure the security and safety of diplomatic representative of the sending state. If it is violated, the sending state shall have the right to invoke the responsibility of the receiving state in accordance to the Draft Articles on Responsibility of States for Internationally Wrongful Acts 2001. In the case of the shooting of Russian ambassador in Turkey, Russia shall have the right to invoke the responsibility of Turkey, but Russia declared that the shooting was a pure provocation by a third party. The two states were cooperating on the investigation, and the results alongside with the evidences obtained shows that the suspect is linked to the Gülenist Terror Group (FETÖ). Keywords: Responsibility of States, Protection and Safety, Diplomat, Shooting of Russian Ambassador * Student of Faculty of Law University of North Sumatera ** Advisor Lecturer I of Faculty of Law University of North Sumatera *** Advisor Lecturer II of Faculty of Law University of North Sumatera